Enhancing Students’ Mathematical Concept Understanding Ability through Augmented Reality Based Learning Media - Fitriyanti S. Lameo; Tedy Machmud; Auli Irfah ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
The mathematical concept understanding ability of eighth-grade students at SMP Negeri 1 Botupingge on cube and block topics remains low, with daily average scores only reaching 28.57% over the past three years due to monotonous conventional learning and a lack of interactive media. The use of Augmented Reality (AR)-based media is proposed as an innovative solution to visualize 3D objects more concretely.​ This study aims to improve the mathematical concept understanding ability of class VIII-C students through the implementation of AR-based learning media on cube and block materials. This Classroom Action Research (CAR) using the Kemmis and McTaggart model was conducted with 24 students from the 2025/2026 academic year at SMP Negeri 1 Botupingge in September 2025. Data collection techniques included observations of teacher and student activities as well as concept understanding tests, conducted over two cycles (planning, implementation, observation, reflection). The AR media enabled student interaction with 3D cube and block models via a mobile application. Data analysis employed average percentage formulas for observation scores and learning completeness (KKM 75).​ Cycle I results showed concept understanding at 59.68%, teacher activities at 72.53%, and student activities at 64.62%, all below the 80% success indicator. After improvements in Cycle II, significant increases were observed to 83.3% (concept understanding), 96.07% (teacher activities), and 97.7% (student activities), with 20 out of 24 students (83.3%) achieving KKM completeness.​ In conclusion, AR-based learning media effectively enhances students' mathematical concept understanding. This improvement is supported by more interactive learning activities and optimal teacher management.